SAT0527 DOPPLER IN ENTHESES: A POTENTIAL USEFUL OUTCOME IN ACTIVE SPONDYLOARTHRITIS AND PSORIATIC ARTHRITIS. (June 2019) - Collada, Juan Molina; Macía-Villa, Cristina; Plasencia, Chamaida; Peiteado, Diana; Nuño, Laura; Monjo, Irene; Villalva, Alejandro; Tornero, Carolina; Bogas, Patricia; Coronel, Luis; González, Gabriela; Benavent, Diego; et al.
Abstract : Background: The assessment of activity in spondyloarthritis (SpA) and psoriatic arthritis (PsA) involves several domains, including entheses. Clinical enthesitis has shown low sensitivity, specificity and reliability. The inclusion of ultrasound (US) could be an objective outcome in the assessment of the disease. Objectives: To assess the prevalence of peripheral US enthesitis using an US score, at patient level, among active SpA and PsA patients. Methods: A cross-sectional study in patients with SpA and PsA active disease (defined as patients proposed to start or switch biological therapy according to physician criteria and in agreement with clinical guidelines) was undertaken. Basal assessment included clinical features, physical examination and laboratory tests. Patients underwent bilateral US examination of peripheral entheses according to the MAdrid Sonographic Enthesitis Index (MASEI). MASEI and OMERACT enthesitis Power Doppler (PD) definitions were checked. Each enthesis was scanned in both the longitudinal and transverse planes, and 5 second videos were recorded for reliability. An inter-reader analysis by three readers was performed. For statistical analysis Mann-Whitney U test, Kruskal-Wallis test and intraclass correlation coefficients (ICCs) were used. Results: 36 patients were included, of whom 19(52.8%) were ankylosing spondylitis (AS) patients, 10(27.8%) PsA, and 7(19.4%) non radiographic axial spondyloarthritis (nr-axSpA). Mean age was 49.8±13.1 years and 18(50%) were females. Mean DAS28 (3.5±1.3), ASDAS (3.7±0.9), BASDAI (5.7±2.2) and CRP values (11.5±12.6) reflect moderate-high disease activity. Demographic and clinical baseline characteristics are shown in Table 1 . Mean global MASEI score was 28.1(±9.1) and 30 patients (83.3%) scored ≥18 (proposed cut-off point to diagnose SpA). Abnormal US findings consistent with at least one enthesis showing PD signal (whether using MASEI or OMERACT PD definition) were observed in 29(80.6%) of patients while two or more PD in entheses were observed in 21(58.3%) patients (PD MASEI definition) or 18(50%) patients (PD OMERACT definition), without significant variation among the different SpA subtypes. The inter-reader reliability among the three readers was high (mean ICC of 0.85). Table 2 shows the ICC of every reader pair. Conclusion: Presence of PD enthesitis is found in 80% of patients with active SpA and PsA. This finding is independent of SpA subtype and support the usefulness of PD US in the assessment of enthesitis. Disclosure of Interests: Juan Molina Collada: None declared, Cristina Macía-Villa: None declared, Chamaida Plasencia Speakers bureau: Pfizer, MSD, Diana Peiteado: None declared, Laura Nuño: None declared, Irene Monjo: None declared, Alejandro Villalva: None declared, Carolina Tornero: None declared, Patricia Bogas Grant/research support from: non restricted grant from Sanofi, Luis Coronel: None declared, Gabriela González: None declared, Diego Benavent: None declared, Elisa Fernández: None declared, Pablo Rodríguez-Merlos: None declared, Gerardo Napky: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Eugenio de Miguel: None declared